Latent Structure of Antisocial and Borderline Personality Disorders: A Taxometric Research. - de Francisco Carvalho, Lucas; Filho, Nelson Hauck; Pianowski, Giselle; Muner, Luana Comito (Paideia (0103863X), 2019)
Establishing personality disorders as categorical or continuous entities is still an ongoing issue, under examination in both psychiatry and psychology. Regarding antisocial (APD) and borderline (BPD) personality disorders, taxonomic analysis have revealed controversial and, therefore, inconclusive results. This study sought to employ taxometric methods in the investigation of the latent structure of APD and BPD. Taxonomically, indicators related to the APD and BPD of the Dimensional Clinical Personality Inventory (IDCP) were analyzed in a clinical sample (N = 282; 63.5% women, mean age = 38.38, SD = 13.59) and a community sample (N = 7,091; 78.8% women; mean age = 22.20, SD = 8.51). Mean CCFI was 0.276 for APD and 0.401 for BPD. Findings apparently refute the traditional categorical nosography as a viable modeling approach for the latent structure of both disorders, besides clearly suggesting a dimensional structure for APD.